DESIGNING READING MATERIAL THROUGH E-BOOK FOR AGRIBUSINESS STUDENTS OF KH. A. WAHAB HASBULLAH UNIVERSITY - Rohmat Hidayat (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2021)
In this era, mastering English is not only focused for English students. It also applies to non-English students. But in the reality, most of them don't particularly like English. This is due to the lack of support of interesting learning media and according to their needs. By developing interesting learning media, students will be more interested in learning English. This research is aimed to design learning media in the form of e-books for Agribusiness students. The researchers designed this book by taking reading skills. To test the feasibility of the E-book, this research and development was conducted. The researchers applied Research and Development (R&D) methods and used ADDIE (Analyze, Design, Development, Implementation, and Evaluation) as the model of the research. To gather the data, the researchers using a data-gathering instrument in the form of questionnaire. The instrument of this research was an interview with the head of the Agribusiness Program. Then, the researchers also distributed questionnaires to 15 Agribusiness students from the Faculty of Agriculture. The students are in the in fourth semester 4 in their program. The data was obtained using questionnaires and obtained 4.13 results for media validation and material validation 3.13 with the category "good." It can be determined that the E-book is worth using for Agribusiness students. KEYWORDS: Reading skill, E-book, Learning media